Broadband Inversion PELDOR Spectroscopy with Partially Adiabatic Shaped Pulses1. Issue 12 (19th February 2013) - Spindler, Philipp E.; Glaser, Steffen J.; Skinner, Thomas E.; Prisner, Thomas F.
<x xml:space="preserve">Abstract</x> Distance and spins: A new broadband, frequency‐selective inversion pulse has been devised for pulsed electron–electron double resonance (PELDOR) spectroscopy, a unique method used to determine distance distributions between two or more paramagnetic centers 2–10 nm apart. The PELDOR modulation depth can be increased by substituting the rectangular pump pulse by a shaped pulse.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>